The Blackadder 1 der historischen Serie erster Teil - Shardlow, Martin; Posner, Geoff; Dudman, William; Atkinson, Rowan; Robinson, Tony; Blessed, Brian (Universal, 2005)
"Blackadder" is one of finest examples of brilliant British sitcom. Razor sharp and extremely funny scripts have been combined with outstanding comic acting to produce a very superior sitcom. It is perhaps therefore not surprising it has been named the second best British sitcom ever. The unique way the same memorable and likeable characters are transported through time for each new series adds to the fun. [www.sitcom.co.uk]